Ambitiosa mors : suicide and self in Roman thought and literature - Hill, Timothy, 1973- (Routledge, 2004)
Annotation Although the distinctive - and sometimes bizarre - means by which Roman aristocrats often chose to end their lives has attracted some scholarly attention in the past, most writers on the subject have been content to view this a s an irrational and inexplicable aspect of Roman culture. In this book, T.D. Hill traces the cultural logic which animated these suicides, describing the meaning and significance of such deaths in their original cultural context. Covering the writing of most major Latin authors between Lucretius and Lucan, this book argues that the significance of the 'noble death' in Roman culture cannot be understood if the phenomenon is viewed in the context of modern ideas of the nature of the self.
Keywords: Suicide -- Rome.; PSYCHOLOGY -- Suicide.; Suicide; Rome (Empire)